Chitosan nanoparticles for daptomycin delivery in ocular treatment of bacterial endophthalmitis - Silva, Nádia C. (2021)
Context: Chitosan nanoparticles were prepared to encapsulate daptomycin and proposed as a delivery system of this antibiotic to the eye for the treatment of bacterial endophthalmitis. Objective: The aim of this study was to develop daptomycin-loaded nanoparticles to apply directly to the eye, as a possible non-invasive and less painful alternative for the treatment of endophthalmitis, increasing the effectiveness of treatment and reducing toxicity associated with systemic administration.Materials and methods: Nanoparticles were obtained by ionotropic gelation between chitosan and sodium tripolyphosphate (TPP). Physicochemical and morphological characteristics of nanoparticles were evaluated, as well as determination of antimicrobial efficiency of encapsulated daptomycin and stability of the nanoparticles in the presence of lysozyme and mucin.Results: Loaded nanoparticles presented mean particle sizes around 200 nm, low polydispersity index, and positive zeta potential. Morphological examination by scanning electron microscopy (SEM) confirmed their small size and round-shaped structure. Encapsulation efficiency ranged from 80 to 97%. Total in vitro release of daptomycin was obtained within 4 h. Determination of minimum inhibitory concentrations (MICs) showed that bacteria were still susceptible to daptomycin encapsulated into the nanoparticles. Incubation with lysozyme did not significantly affect the integrity of the nanoparticles, although mucin positively affected their mucoadhesive properties. Discussion and conclusion: The obtained nanoparticles have suitable characteristics for ocular applications, arising as a promising solution for the topical administration of daptomycin to the eye.